First experimental observation of the conical effect in Smith–Purcell radiation; JETP Letters; Vol. 105, iss. 9 - Naumenko G. A. Gennadiy Andreevich; Potylitsyn A. P. Alexander Petrovich; Sergeeva D. Yu. Darjya Yurjevna; Tishchenko A. A. Aleksey Aleksandrovich; Strikhanov M. N. Mikhail Nikolaevich; Bleko V. V. Vitold Vladislavovich (2017, 2017)
Title screen